Managing DMNCs: A search for a new paradigm - Doz, Yves; Prahalad, C. K. (Strategic Management Journal, 1991)
This article reviews and assesses the contribution, explicit or implicit, of various schools of organization theory to the development of a stream of research on the management of multinational companies, and summarizes what is seen as the emerging paradigm of multinational management. While the contribution of some of the schools has been substantial, we conclude that opportunities for more cross-fertilization between organization theorists and scholars of multinational strategic management have been missed, mainly because the differences between theory development and phenomenological understanding have seldom been bridged.